Self-Efficacy as A Correlate of Pupils' Academic Achievement in Mathematics - K. E. Obafemi; U. T. Saadu; A. Adesokan; O. Yahaya; J. T. Sulaimon; T. O. Obafemi; F. M. Yakubu (Universitas Pendidikan Indonesia, 2023)
The study examined the self-efficacy of pupils' academic achievement in mathematics. The study adopted a correlational research design. A simple random sampling technique was used to select 568 pupils from 14 public primary schools in the research locale. Two research instruments were used for data gathering. The instruments were the Questionnaire on Pupils' Self-efficacy (QFYPS) and Mathematics Achievement Test (MAT). One research question was raised while two hypotheses were postulated. QFYPS and MAT were validated by lecturers in the Department of Early Childhood and Primary Education, Kwara State University, Malete, Nigeria. QFYPS and MAT were also tested for reliability using the test-retest method and the reliability coefficients were 0.79 and 0.77 respectively. The research question was answered using Pearson Product Moment Correlation (PPMC) while the two hypotheses were tested using Independent samples t-test. The findings of the study showed that there was a positive relationship between pupils' self-efficacy and their academic achievement in mathematics. Also, there was no significant difference in the self-efficacy of pupils based on gender. Finally, there was no significant difference in the academic achievement of pupils based on gender. Based on the findings of the study, it was recommended that Teachers and policymakers should implement strategies that enhance pupils' self-efficacy beliefs in mathematics.